Perfil das Cirurgias Cardíacas Valvares no Brasil Análise do Registro Bypass - Zilli, Alexandre Cabral [UNIFESP] (2019)
BACKGROUND: Valvular heart diseases are the second cause of cardiac surgeries in the world. However, the patients’ profile, etiology of valve diseases and surgical results differ according to the population and country studied. In Brazil, the BYPASS (Brazilian Registry of Cardiovascular Surgeries in Adults) project aims to map the epidemiological aspects and results of surgical treatment of patients with heart disease. OBJECTIVE: To analyze the profile of valvular heart surgery performed in Brazil, using the BYPASS Registry database. METHOD: A multicenter observational / prospective cohort study with 17 participating centers in Brazil. We evaluated 920 patients submitted to cardiac valve surgeries isolated and / or associated from August 2014 to April 2018. Postoperative clinical outcomes: cardiopulmonary and infectious complications, length of stay in the Intensive Care Unit and hospital in the post-operatory and mortality, compared to estimated calculated mortality risk by EuroSCORE (European System for Cardiac Operative Risk Evaluation). RESULTS: The mean age of the patients was 56.7 years and women represented 47%. Isolated aortic valve replacement was the most frequently performed surgery (34%), followed by isolated mitral valve replacement (24.9%) and double-mitro-aortic valve replacement (13.3%). Valve repair was performed in 21% of mitral procedures. Minimally invasive access was performed at 1.6%. Invasive mechanical ventilation post-op >24hours occurred in 8.2%. The most frequent postoperative complications were arrhythmias (22,6%), infections (5.7%- 27% in surgical focus) and low-output syndrome (5.1%). Surgeries by the public system (Unique Health System) accounted for 80.8%. The hospital mortality rate was 7.3%, while mean logistic EuroSCORE was 7.9%. The rheumatic etiopathogenesis occurred in 38.3% of the operated patients. CONCLUSION: The most frequent isolated valve surgery in Brazil is the aortic valve replacement by conventional open access, followed by mitral valve replacement surgery and double valve replacement. Rheumatic disease was the main ethiopathogenic cause of valve surgeries in Brazil. Hospital mortality of valvular cardiac surgeries match corresponding logistic risk stratification by EuroScore, showing a medium to high risk population operated. The BYPASS registry became a fundamental tool to know the profile of patients with valve heart disease in our country in order to delineate adequate strategies for health promotion and resource allocation for cardiac surgery.